The Rule of Law in a Multi‐State Dimension: The Rule of Law and Private International Law - Tamás Szabados (University of Bologna Law Review)
In the legal literature, the rule of law has been often considered a public law phenomenon and little attention has been paid to the relationship between the rule of law and private international law. This article outlines how the rule of law has unfolded in private international law and how it influences the creation and application of private international law rules. Savigny’s private law theory detached law from state power which led to the recognition of the equality of the legal systems from the point of view of the designation of the applicable law. The classic conflict of laws method focused on legal certainty in determining the governing law that corresponds to a formal conception of the rule of law of the eighteenth and nineteenth century. Today’s private international law, however, also enables the infiltration of the material values of the rule of law into private international law, in particular through the public policy clause or as overriding mandatory norms. The development of European Union (EU) private international law illustrates this well. The public policy exception is suitable to prevent the application of the otherwise governing foreign law or the recognition and enforcement of a foreign decision that is contrary to the fundamental principles of the domestic legal order of the state of the forum, including human rights. Moreover, the lack of judicial independence in an EU Member State where a decision was rendered can result in the denial of recognition and enforcement of that decision in another Member State not only in criminal but also in civil matters. The requirements of the rule of law, and in particular the respect for human rights also influence the methodology of private international law. As the legal literature points out, the method of recognition, requiring the recognition of legal status acquired abroad irrespective of the law designated by the conflict of laws rules of the forum, coexists with the traditional conflict of laws method.